Biofortification of Potato and Carrot With Iodine by Applying Different Soils and Irrigation With Iodine-Containing Water - Dobosy, Péter; Endrédi, Anett; Sandil, Sirat; Vetési, Viktória; Rékási, Márk; Takács, Tünde; Záray, Gyula (Frontiers in Plant Science, 2020)
Accumulation of iodine by potato (Solanum tuberosum L.) and carrot (Daucus carota L. var. sativus) plants cultivated on different soils (sand, sandy silt, silt) using irrigation water containing iodine at concentration of 0.1 and 0.5 mg/L was investigated. In the edible organs of potato and carrot control plants grown on sand, sandy silt and silt soils the iodine concentrations were 0.15, 0.17, 0.20 mg/kg (potato) and 0.012, 0.012, 0.013 mg/kg (carrot), after the treatment by applying 0.5 mg/L iodine dosage, the iodine concentrations were 0.21, 0.19, 0.27 mg/kg (potato) and 3.5, 3.7, 3.0 mg/kg (carrot), respectively. Although the iodine treatment had no significant effect on the biomass production of these plants, in potato tubers it resulted in higher Fe and lower Mg and P concentrations, whereas no similar trend was observable in carrot roots. The accumulation of Mn, Cu, Zn, and B in the edible part of both plants was not influenced by the iodine treatment. The soil properties did not have significant impact on the biomass production under the same environmental conditions. The concentration and distribution of iodine in both plants were slightly modified by the growing medium, however, the photosynthetic efficiency and chlorophyll content index of potato plants cultivated in silt soil increased significantly. Potato plant was not suitable for biofortification with iodine, while considering the iodine concentration and moisture content of carrot roots, it can be calculated that consuming 100 g fresh carrot would be cover about 38% of the daily iodine intake for an average adult person.